Evaluation Dyslipidemia and Resistin in Diabetic Obese Patients in Mirpur AJK (Medical Forum Monthly, 2024)
Objective: .This study was planned to compare and correlate the potential role of resistin in obese patients with T2DMStudy Design: Comparative studyPlace and Duration of Study: This study was conducted in Pharmacology and Biochemistry Department of Mohtarma Benazir Bhutto Shaheed Medical College Mirpur-AJK from April 2016 to November 2017.Materials and Methods: In this study we also collaborate with Medicine department of DHQ Hospital of Mirpur AJK. In this study we had taken 120 (Eighty) male and female obese patients. Pregnant women were not considered in study. We also ensured that patients had taken any medicine. In our study, we select the range of patient from thirty six to fifty nine year (36 to 59).Results: In type 2 diabetic patients we found high level of Serum resistin i.e. (38±8 ng/ml) as compare to controls. Serum cholesterol (206.2 ± 69 mg/dl), serum triglycerides (184.3 ± 73mg/dl), serum LDL(165.4 ± 36mg/dl) was significantly higher in diabetic obese Patients. Serum HDL (39.1 ± 14) mg/dl) was significantly low in diabetic subjects. Our study showed that cholesterol, triglyceride (TG) and low density lipoprotein (LDL) are found higher in obese diabetic patients as compared to obese controls. Resistin, total cholesterol and LDL-cholesterol were not exist significantly in obese diabetic patients when we compared the result with obese controls. But on other side we observed the results of TG (triglycerides) is significant higher in obese diabetic patients as compare obese controls. it means that there is positive correlation present between TG (triglycerides) and obese diabetic patient.Conclusion: Lipid profile is disturbed with resistin which ultimately caused to insulin resistance in diabetes mellitus in obese subjects. We should try to control hormone such as resistin will be helpful to control diabetic obese patients with dyslipidemia